2D New Nonmetal Photocatalyst of Sulfur‐Doped h‐BN Nanosheeets with High Photocatalytic Activity. Issue 7 (25th February 2019) - Zhao, Gang; Wang, Aizhu; He, Weidong; Xing, Yupeng; Xu, Xijin
Abstract: 2D nonmetal hexagonal boron nitride nanosheets (h‐BNNS) are attracting more attention in the field of catalysis due to their excellent adsorption and photooxidation resistance performances. Here, for the first time, the possible adjustment of the bandgap of h‐BNNS (4.13 eV) by doping sulfur atoms is theoretically demonstrated and experimentally realized, which causes h‐BNNS (no photocatalytic property) to possess impressive visible light photocatalytic properties. The photodegradation efficiency (η) of S‐BNNS for rhodamine B reaches 97.2% for 3 h, and the photocatalytic hydrogen production efficiency is 1348.5 µmol h −1 g −1, which are higher than those of the common visible light photocatalysts (S and g‐C3 N4 ). This approach is of guiding significance for the application of h‐BNNS in the field of photocatalysis. Abstract : 2D nonmetal hexagonal boron nitride nanosheets (h‐BNNS) are attracting catalysis yield attention due to their excellent adsorption and photooxidation resistance performances. Here, for the first time, it is theoretically and experimentally demonstrated that the bandgap of h‐BNNS is adjusted by doping sulfur atoms, which causes h‐BNNS (no photocatalytic property) to possess excellent visible light photocatalytic properties (photodegradation and hydrogen production).